Design of DSS The Best Employee Performance Using Analytical Hierarchy Process UML Based - Rizaldi Rizaldi; Dewi Anggraeni (The IJICS (International Journal of Informatics and Computer Science), 2021)
Employees are a highly needed human resource. In order to achieve the desired goals, the agency conducts the best performance appraisal of employees. The Analytical Hierarchy Process method is a method for determining criteria and choice alternatives, followed by calculating the eigenvector value and testing its consistency. The application of analytical hierarchical analysis of the best employee performance appraisal process, where the results of this assessment can encourage every employee to give the best performance to the agency. The best employee performance decisions are made at the ambalutu village hall office. There are several criteria for performance appraisal, namely communication skills, honesty, cooperation, and person. Analysis method analytical hierarchy process where each criterion will be assessed in pairs comparison with other criteria to get priority value. In this study the results of the ratio were 0.07, which means that the assessment was consistent because it was less than 0.1, so the percentage of communication values was 40%, honesty 34%, cooperation 17% and personal 10%.